BMP implant associated with platelet-rich plasma in orbit fracture repair - Ferraz, Fabio Henrique [UNESP]; Schellini, Silvana Artioli [UNESP]; Schellini, Ricardo Campos [UNESP]; Pellizzon, Claudia Helena [UNESP]; Hirai, Flavio Eduardo [UNESP]; Padovani, Carlos Roberto [UNESP] (Taylor & Francis, 2008)
Purpose: To evaluate a bone morphogenetic protein (BMP) implant with and without platelet-rich plasma (PRP), which is supposed to accelerate fracture consolidation in the orbit fracture treatment. Methods: Thirty-six white rabbits were subjected to orbital fracture and treated in three groups: BMP implant fracture repair (G1), BMP plus PRP implant fracture repair (G2), and fracture and spontaneous repair (G3). The animals were sacrificed at 7, 30, 90, and 180 days after surgery. A radiology evaluation was carried out on the 7th day after the fracture and at the sacrifice moments. After the animals' death, the orbital content material was removed and prepared for morphological and morphometric analysis. Results: Radiology suggested intramembranous and progressive cavitation and ossification without a reduction in implant size and with signs of calcium deposition; these events were confirmed by histological analysis, which showed a lymphomononuclear inflammatory reaction in G1 and G2, more intense 7 days after surgery and reducing after 30 days. Associating PRP with BMP did not accelerate bone induction. Conclusion: BMP implant promotes bone induction, integration at fracture site, scarce inflammatory reaction, and may be a good alternative in orbit fracture reconstruction. The addition of PRP to the BMP plate did not accelerate the resolution, and its use is not necessary. Copyright © Informa Healthcare USA, Inc.
Keywords: Experimental; Morphogenetic protein; Orbital fracture; Platelet-rich plasma histology; Radiological evaluation; bone morphogenetic protein; animal; bone development; bone regeneration; bone transplantation; disease model; drug effect; injury; male; multimodality cancer therapy; orbit; orbit fracture; pathology; rabbit; radiography; thrombocyte rich plasma; wound healing; Animals; Bone Morphogenetic Proteins; Bone Transplantation; Combined Modality Therapy; Disease Models, Animal; Male; Orbit; Orbital Fractures; Osseointegration; Osteogenesis; Platelet-Rich Plasma; Rabbits; Wound Healing